The Effect of a Thromboxane Synthetase Inhibitor, Dazoxiben, and Acetylsalicylic Acid on Platelet Function and Prostaglandin Metabolism - Dale, Jon; Thaulow, Erik; Myhre, Erik; Parry, John (Thrombosis and Haemostasis, 1983)
Twenty-four men received either placebo, 0.1 g of the thromboxane synthetase inhibitor dazoxiben, 0.25 or 1.0 g of acetylsalicylic acid (ASA). Dazoxiben reduced the maximal rate of collagen-induced platelet aggregation, but less than did ASA. ASA abolished secondary, ADP-induced aggregation, dazoxiben not. Both drugs prolonged the bleeding-time.Plasma thromboxane B2 (TxB2) levels did not change significantly after dazoxiben, whereas the prostacyclin metabolite 6-keto-PGF1α rose. The larger dose of ASA reduced both TxB2 and 6-keto-PGF1α in plasma. Whole blood was allowed to clot in order to estimate prostaglandin metabolism. Both drugs prevented thromboxane production effectively. Formation of 6-keto-PGF1α decreased by 95 per cent after ASA but was more than doubled after dazoxiben.Dazoxiben is a selective and effective thromboxane synthetase inhibitor, but has a weaker effect on platelet reactivity than ASA, possibly because endoperoxide formation is not prevented.
Keywords: Thromboxane synthetase inhibition; Cyclo-oxygenase inhibition; Thromboxane; Prostacyclin; Platelet function